Molecular assessment of predation by hoverflies (Diptera: Syrphidae) in Mediterranean lettuce crops - POLO, PRISCILA GOMEZ; Gomez-Polo, PRISCILA GOMEZ; Alomar, Oscar; Castane, Cristina; Lundgren, Jonathan G.; Pinol, Josep; Agusti, Nuria (My University, 2015)
BACKGROUNDHoverflies (Diptera: Syrphidae) are generalist predators of a great variety of pests. Nasonovia ribisnigri (Hemiptera: Aphididae) and Frankliniella occidentalis (Thysanoptera: Thripidae) are two common pests in Mediterranean lettuce crops, where they occur alongside alternative prey (e.g. Collembola). A semi-field experiment was conducted in an experimental lettuce plot where hoverfly predation on N. ribisnigri, F. occidentalis and Collembola was studied by conventional PCR and qPCR using specific primers, as well as by next-generation sequencing (NGS) in order to reveal other potential trophic interactions.